Hydrocarbon Degrading Microflora in a Tropical fuel-Contaminated Aquifer: Assessing the Feasibility of PAH Bioremediation - Castro Gutiérrez, Víctor Manuel (2012)
An aquifer located within a petroleum processing plant in Moín, Costa Rica, suffers hydrocarbon pollution. This study aimed to determine the ability of indigenous microorganisms from this site to degrade polycyclic aromatic hydrocarbons (PAHs) to evaluate the feasibility of an eventual bioremediation process. Aerobic conditions were found in the aquifer, while microbial analyses of the groundwater indicated the presence of important hydrocarbon-degrading populations. Sixteen PAH-degrading strains were isolated with the ability to grow on naphthalene (5 strains), phenanthrene (3), fluorene (6) and pyrene (2). Most of the identified isolates belonged to the genus Pseudomonas, although, Comamonas, Sphingomonas Stenotrophomonas and Delftia were also found. A mixture of selected strains was evaluated by its performance of PAH degradation in soil-slurry systems, where efficiency of removal was naphthalene > fluorene > phenanthrene > pyrene. This study is an initial approach to evaluate the feasibility of applying a bioremediation process in the contaminated site.